MANAGEMENT OF AN ECTOPIC PERMANENT LATERAL INCISOR IN A CHILD'S CHIN - Kone K; Kouame KB; Kone M; Savi De Tove M; Oka AE; Kattie AL; Forna NC; Songo FB (Romanian Society of Oral Rehabilitation, 2023)
Introduction: Tooth eruption anomalies occur in both temporary and permanent teeth. They also affect all maxillary and mandibular teeth, in particular the incisors. Localization outside the maxilla is a rare phenomenon, with psychological, functional and above all aesthetic consequences. In traditional African society, mystical considerations can be evoked to explain it. The aim was to manage an ectopic permanent incisor located on the chin, in order to avoid the disturbances that can occur in children. Case presentation: This was an 11-year-old child whose lower permanent incisor had erupted outside the mandibular bone, in the cellular tissue of the chin arch, outside the chin and lower lip muscles. Treatment: it consisted of extraction of the affected tooth, followed by suturing of the wound and antibiotic therapy. This treatment not only restored aesthetics and function, but also prevented the marginalization of the young patient. Conclusion: This case study highlights the need for aesthetic, psychological and functional management to ensure the patient's well-being and overall development.